Strategic Euphemism and National Face-Work: A Sociolinguistic Study of Lincoln’s Gettysburg Addresss - Pasaribu, Uswatun Rafi'a; Batubara, Vinjellina; Ahmad, Sophie meilatifah; Rangkuti, Rahmadsyah (Pusat riset dan Inovasi Nasional, 2025)
This study examines the strategic role of euphemism in Abraham Lincoln’s Gettysburg Address, arguing that it was instrumental not only in managing collective grief but also in preserving the nation’s symbolic dignity. While much scholarship on the Gettysburg Address has concentrated on rhetorical artistry or historical significance (Wills, 1992; White, 2009), relatively few have analyzed it through the combined lens of sociolinguistics, specifically euphemism and face-work. Drawing on Allan and Burridge’s (2006) framework of euphemism and Goffman’s (1955) theory of face, this paper situates Lincoln’s speech within the broader sociolinguistic processes of healing, unity, and image restoration. Through a qualitative textual analysis, the study identifies three dominant euphemistic strategies: sanctification of sacrifice through sacred language, collectivization through inclusive pronouns, and redefinition of crisis as a “new birth of freedom.” These strategies operated at semantic, pragmatic, and sociopolitical levels to protect national face, transform perceptions of the Civil War, and realign public consciousness toward unity and resilience. Beyond historical interpretation, this research highlights the relevance of euphemism and face-work in contemporary political communication. Leaders in modern contextsfrom economic crises to global pandemics continue to rely on euphemistic framing to manage uncertainty and inspire solidarity. By revisiting Lincoln’s address through this sociolinguistic perspective, the study demonstrates how language can simultaneously mitigate trauma, construct identity, and articulate a hopeful collective future.